2014
DOI: 10.1007/s00259-014-2856-x
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET of the hands with a dedicated high-resolution PEM system (arthro-PET): correlation with PET/CT, radiography and clinical parameters

Abstract: Purpose The aim of this study was to prospectively determine the feasibility and compare the novel use of a positron emission mammography (PEM) scanner with standard PET/CT for evaluating hand osteoarthritis (OA) with 18F-FDG. Methods Institutional review board approval and written informed consent were obtained for this HIPAA-compliant prospective study in which 14 adults referred for oncological 18F-FDG PET/CT underwent dedicated hand PET/CT followed by arthro-PET using the PEM device. Hand radiographs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…However, typical OA lesions ( Figure 1B, in DIP joints) incorporated 18 F-NaF but not 18 F-FDG, though DIP joints were not systematically assessed in this study. Moreover, according to previous reports, some OA lesions take up 18 F-FDG [34,38]; therefore, secondary synovitis is likely accompanied by OA.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…However, typical OA lesions ( Figure 1B, in DIP joints) incorporated 18 F-NaF but not 18 F-FDG, though DIP joints were not systematically assessed in this study. Moreover, according to previous reports, some OA lesions take up 18 F-FDG [34,38]; therefore, secondary synovitis is likely accompanied by OA.…”
mentioning
confidence: 70%
“…Specificity to detect bone lesions is greatly improved by introduction of SPECT/CT, but further significantly improved with use of 18 F-NaF PET/CT [23,34].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The system provided tomographic sampling, and attenuation and scatter correction of PET data employed the co-registered CT image. Recently, the feasibility of the quad-highdensity avalanche chamber nano-PET small-animal system, 31 the positron emission mammography Flex Solo II system 32,33 and the avalanche photodiode (APD)-based BrainPET system (Siemens Healthcare, Erlangen, Germany) 34 was demonstrated for wrist and hand arthritic imaging. These systems, however, did not have direct means for attenuation and scatter correction, and therefore radiotracer activity quantification is challenging.…”
Section: Fluorine-18 Fludeoxyglucose Uptake For the First Carpometacamentioning
confidence: 99%
“…A study compared 18F-fluoride PET and MRI in evaluating early-stage hip OA and found 18F-fluoride PET could detect bone abnormalities earlier than MRI 17 . Another PET study reported higher joint 18F-fluorodeoxyglucose uptake in hand OA, relative to normal controls 18 . Such methodology may be useful in mechanistic studies in OA.…”
Section: New Lessons From Nuclear Medicine Pet May Detect Early Bone mentioning
confidence: 95%